DEVELOPMENT OF ZIF-8 LOADED PVA HYBRID MEMBRANES FOR THE DESALINATION OF SEAWATER BY PERVAPORATION - Sığın, Zeynep; Güvenç, Gözdenur; Çakmakçı, Nagihan; Ünlü, Derya (Kahramanmaras Sutcu Imam University, 2022)
In this study, ZIF-8 zeolitic imidazolate framework was synthesized and added to the polyvinyl alcohol (PVA) membrane for the manufacture of hybrid membranes to use in pervaporative desalination. The hybrid membranes were characterized by using FTIR, SEM and contact angle. The effects of ZIF-8 loading ratio, feed NaCl concentration, and operation temperature on separation perfomance were investigated. The addition of ZIF-8 to the improved the hydrophilicity and purification performance of membrane. The optimal loading ratios ZIF-8 were specified as 0.25 wt%. Optimum operation parameters were found as 60oC of temperature and a 2 wt% of feed NaCl concentration. Pervaporative desalination tests of seawater were carried out under the optimum operation conditions and rejection performance of >99.99% were achieved. The obtained data are observed under the drinking water standart values of World Health Organization. Hybrid membranes which are exhibited rather successful separation performance, are candidate structure for the usage of desalination process.

Bu çalışmada ZIF-8 zeolitik imidazolat kafes yapısı sentezlenmiş ve polivinilakol (PVA) membrana eklenerek pervaporatif desalinasyon için hibrit membranlar üretilmiştir. Hibrit membranlar FTIR, SEM ve temas açısı ile karakterize edilmiştir. ZIF-8 yükleme oranının, besleme tuz konsantrasyonunun ve operasyon sıcaklığının membranın ayırma performansına etkisi incelenmiştir. ZIF-8 ilavesinin membranın hidrofilitesini ve ayırma performansını iyileştirildiği görülmüştür. Optimum ZIF-8 yükleme oranı ağırlıkça %0.25 olarak belirlenmiştir. Optimum operasyon parametreleri ise 60oC sıcaklık ve ağırlıkça %2 besleme tuz konsantrasyonu olarak bulunmuştur. Optimum operasyon koşulları altında deniz sularının pervaporatif desalinasyon testleri yapılmış ve %99’un üzerinde giderim performansı elde edilmiştir. Elde edilen verilerin Dünya Sağlık Örgütü’nün içme suyu standart değerlerinin altında kaldığı görülmüştür. Hibrit membranların oldukça başarılı bir ayırma performansı sergileyerek, desalinasyon prosesi için kullanılmaya ve geliştirilmeye aday bir yapıya sahip olduğunu sonucuna varılmıştır.
DENİZ SUYUNUN PERVAPORASYON İLE DESALİNASYONU İÇİN ZIF-8 YÜKLÜ PVA HİBRİT MEMBRANLARIN GELİŞTİRİLMESİ
220Y022
Keywords: Engineering; Mühendislik